Typology Model Based Building and Land Infrastructure Structure Organization and Duties Bali Area Police - Ni Ketut Natalia Wulansari; I Nengah Sinarta; Agus Kurniawan (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
Polsek was a police station in the district that provides police services to the community. There are four types of Polsek, namely A, B, C, and D. Polsek in the Bali Area are 58 with types B and C. Polsek is expected to have adequate supporting infrastructure such as Integrated Police Service Center rooms, facilities for the disabled, children's playgrounds, breastfeeding rooms, detention cells, and parking, open spaces. However, the land area is only sometimes adequate. The analysis used interview methods, observation, literature studies, and SWOT analysis. The results show that Polsek's need for land Type B is 631.54 m2, and Type C is 377.14 m2. The SWOT analysis was in the strength and threat quadrant, so a policy is needed to evenly distribute the development of each Polsek type B and C, starting from land acquisition by the main tasks and functions of the police in serving the community.